INTERPRETASI DATA RESISTIVITAS UNTUK MENGIDENTIFIKASI MUNCULNYA LONGSOR SUSULAN DI BLOK V WAYAME AMBON - Sapulete, Sisca M.; Souisa, Matheus; Jubaedah, Sitti (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2019)
Research of the Block V Wayame Ambon slide planes has been carried out using the geoelectric resissivity method of the Wenner-Schlumberger configuration. The purpose of the study was to estimate the structure of the subsurface rock layer and identify the distribution of slide plane based on the cross section of rock resistivity. The rock resistivity modeling results show the existence of a slip zone on both measurement trajectories. On the Line-1 it was assumed that two slide planes found at a depth of 2.0 m located at a distance of 6.0 m and 38.0 m, while on the Line-2 the slide planes are in 2.5 m depth is located at a distance of 28.0 m. The slip zone which is a landslide-prone area lies in the intermediate resistivity group (30-70 W.m) with the type of sand or clay sand which overlaps the high resistivity group (> 70 W.m) in the form of a hard claystone (bedrock). Landslide-prone zones can have the potential for a subsequent landslide to occur by allowing the potential spread of landslides to remain at their original location in the event of disturbances on the slopes and the opportunity to shift towards the top of the slope.